Pharmaceutical care in the management of inhalers in patients with bronchialasthma - Tiza, Delia H. (2019)
Was the literature review of therapy by inhalation in the treatment of respiratory diseases; chronic obstructive puhnonary disease (COPD), asthma, chronic bronchopulmonary, with a growing interest in using it in other pathologies whose target organ is the lung infections. However, the precise medication in the proper use of inhalers, leam about disease and medication use to ensure effective treatment. The desire to enhance the proper use of the inhaler makes the patient more anxious and vulnerable for its improvement, the correct use of the inhaler reduces the possible adverse effects. Asthmatic patients, pharmaceutical care shows positive results in the quality of life of the patient. The Chemical Pharmaceutical is the ideal professional to perform pharmaceutical care to patients with asthma by his academic background and experience in care in community pharmacies.